2017
DOI: 10.9790/1959-0603027583
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Perceived stress, Emotional Intelligence and Hope among Intern Nursing Students

Abstract: The internship nursing experience is a valuable prospect for new nurses to gain practice in a real

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In similar, it was stated that there was a strong, negative, and statistically significant relationship between perceived stress and emotional intelligence levels of nursing students (Mousa et al, 2017). According to the year level of nursing students, it was found that there is a negative and statistically significant relationship between the perceived stress and emotional intelligence levels of the first-year nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…In similar, it was stated that there was a strong, negative, and statistically significant relationship between perceived stress and emotional intelligence levels of nursing students (Mousa et al, 2017). According to the year level of nursing students, it was found that there is a negative and statistically significant relationship between the perceived stress and emotional intelligence levels of the first-year nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, resilience was addressed as contributing to health conditions and well‐being in nursing students (Chow et al, 2018 ; Eaves & Payne, 2019 ; Elzohary et al, 2017 ; Hamadeh Kerbage et al, 2021 ; Ríos‐Risquez et al, 2016 ; Serçe et al, 2021 and Spurr et al, 2021 ). Moreover, resilience was connected to the personal growth of nursing students, as they can learn from overcoming adversities and gain a positive outlook for their future (Hasson et al, 2021 ; Liang et al, 2019 ; Lopez et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some demographic characteristics have been shown to affect resilience in nursing students, including inadequate income (Ching & Cheung, 2021 ; Ertekin Pinar et al, 2018 ; Hamadeh Kerbage et al, 2021 ; Yıldırım et al, 2021 ; Yıldız, 2021 ), age (Ching & Cheung, 2021 ; Ertekin Pinar et al, 2018 ; Hasson et al, 2021 ), gender (Arries‐Kleyenstüber, 2021 ; Ching & Cheung, 2021 ), marital status (Yıldırım et al, 2021 ), year of study (Elzohary et al, 2017 ; Fernández‐Martínez et al, 2021 ; Yıldırım et al, 2021 ), religion (Sigalit et al, 2017 ) and living conditions (Yıldırım et al, 2021 ). However, some have argued that age does not affect resilience (Arries‐Kleyenstüber, 2021 ; Grande et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 27 36 37 38 ] A comparable study conducted among nursing students in Damanhur, Egypt reported a mild negative correlation between EI and perceived stress, which was determined to be not significant upon multivariate analysis. [ 39 ] Similarly, another study carried out among psychology students in the United States, which aimed at studying the influence of personality traits on the relationship between EI and stress, did not find any association between the two, across all participants. However, after taking personality traits (such as intensity, clarity and attention) into consideration, the authors concluded that emotional intelligence predicts stress in some people, not all.…”
Section: Discussionmentioning
confidence: 99%